RECOMMENDED READING: AN ANNOTATED BIBLIOGRAPHY OF SOME EXEMPLARY BOOK SELECTIONS IN HUMANIST SOCIOLOGY - Ballard, Chet Ballard; Arcaro, Tom (TRAILS: Teaching Resources and Innovations Library for Sociology, 2010)
Some of the selections are out of print, or hard to find. Several of the items annotated below are currently in print and may be obtained by corresponding directly with the author(s), publishers, or through an e-commerce Internet site like Amazon.com.